Mangiferin induces apoptosis in human ovarian adenocarcinoma OVCAR3 cells via the regulation of Notch3 - Zou, Bingyu (Oncol Rep, 2017)
Ovarian cancer is the most lethal gynecological malignancy in the world. Our previous studies showed that mangiferin, purified from plant source, possessed anti-neoplasm effect on human lung adenocarcinoma A549 cells. This study aimed to determine the apoptosis-inducing effect of mangiferin on human ovarian carcinoma OVCAR3 cells. By in vitro studies, we found mangiferin significantly inhibited viability of OVCAR3 cells, and remarkably increased the sensitivity of OVCAR3 cells to cisplatin. In addition, the activation of caspase-dependent apoptosis was observed in mangiferin treated ovarian cancer cells. Importantly, we observed an obviously downregulated Notch expression after mangiferin treatment, indicating the crucial role of Notch in mangiferin mediated apoptosis. In contrast, overexpression of Notch3 abrogated the apoptosis-inducing efficacy of mangiferin, further demonstrating that mangiferin induced apoptosis via Notch pathway. Furthermore, OVCAR3 cell xenograft models revealed that mangiferin treatment inhibited tumor growth and expanded survival of tumor xenograft mice. Based on these results, we concluded that mangiferin could significantly inhibit the proliferation and induce apoptosis in OVCAR3 cells. Our study also suggested the anti-neoplasm effect of mangiferin might be via the regulation of Notch3. Taken together, by targeting cell apoptosis pathways and enhancing the response to cisplatin treatment, mangiferin may represent a potential new drug for the treatment of human ovarian cancer.